Resveratrol and derivatives for the treatment of atrial fibrillation. (23rd July 2015) - Baczkó, István; Light, Peter E.
Abstract : Resveratrol is a bioactive polyphenol, found in grapes, red wine, and peanuts, and has recently garnered much media and scientific attention for its diverse beneficial health effects as a nutritional supplement or nutraceutical. Of particular interest are the well‐documented cardioprotective effects of resveratrol that are mediated by diverse mechanisms, including its antioxidant and vascular effects. However, it is now becoming clear that resveratrol may also exhibit direct effects on cardiac function and rhythm through modulation of signaling pathways that regulate cardiac remodeling and ion channel activity that controls cardiac excitability. Resveratrol may therefore possess antiarrhythmic properties that contribute to the cardiovascular benefits of resveratrol. Atrial fibrillation (AF) is the most common cardiac arrhythmia, although current therapies are suboptimal. Our laboratory has been studying resveratrol's effects on cardiac ion channels and remodeling pathways, and we initiated a drug development program aimed at generating novel resveratrol derivatives with improved efficacy against AF when compared to currently available therapeutics. This review therefore focuses on the effects of resveratrol and new derivatives on a variety of cardiac ion channels and molecular pathways that contribute to the development and maintenance of atrial fibrillation.